Assessment of Learning Style and Learning Habit on Academic Performance of Agricultural Education Students in Federal University Kashere, Gombe State - Adamu, Y.; Ibrahim , Laraba; Bamusa, H. K. (Kashere Journal of Education, 2025)
This research study aimed to identify the predominant learning styles and prevailing study habits on academic performance of undergraduate students of Agricultural Education in the Federal University of Kashere. A descriptive survey design was employed, and data were collected from respondents by using a structured questionnaire. a stratified random sample technique was used to select 100 students across all academic levels (100–400 level). Descriptive and inferential statistical techniques were used to analyse the data. The findings revealed that visual and auditory learning styles were the most commonly adopted among agricultural education students, while preferred study habits included night reading and regular revision. A significant relationship was found between students’ learning styles and their learning habits, indicating that students often adapt their study behaviours to align with their preferred modes of learning. Moreover, effective and consistent learning habits were found to have a positive influence on students’ academic performance. The study concludes that learning styles and habits are pivotal in shaping academic outcomes. It recommends that students be encouraged to understand and apply their unique learning preferences, while lecturers should incorporate diverse teaching methods that cater to various learning styles. Additionally, institutional support through workshops and curriculum reforms focused on learning strategies is essential. The study acknowledges limitations such as reliance on self-reported data and a single-department scope, suggesting that future research expand across disciplines and consider additional variables like gender and technology use.